2016
DOI: 10.1073/pnas.1522070113
|View full text |Cite
|
Sign up to set email alerts
|

Small-scale societies exhibit fundamental variation in the role of intentions in moral judgment

Abstract: Intent and mitigating circumstances play a central role in moral and legal assessments in large-scale industrialized societies. Although these features of moral assessment are widely assumed to be universal, to date, they have only been studied in a narrow range of societies. We show that there is substantial cross-cultural variation among eight traditional small-scale societies (ranging from hunter-gatherer to pastoralist to horticulturalist) and two Western societies (one urban, one rural) in the extent to w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
225
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 284 publications
(233 citation statements)
references
References 19 publications
7
225
1
Order By: Relevance
“…Identifying universal moral norms in humans is still an ongoing endeavor (e.g., Barrett et al, 2016) but they minimally include the contents of not harming infants, avoiding inequity, caring for one's own offspring, and avoiding incest. Some evidence suggests that they may be present at least in dyadic, but sometimes even in third-party contexts in non-human primates too.…”
Section: Social Norms I: Universal Biologically Anchored Contentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Identifying universal moral norms in humans is still an ongoing endeavor (e.g., Barrett et al, 2016) but they minimally include the contents of not harming infants, avoiding inequity, caring for one's own offspring, and avoiding incest. Some evidence suggests that they may be present at least in dyadic, but sometimes even in third-party contexts in non-human primates too.…”
Section: Social Norms I: Universal Biologically Anchored Contentsmentioning
confidence: 99%
“…However, despite this variability in the content of what counts as moral among cultures, there are also elements that seem universal, both with regard to the proximate mechanisms that regulate moral behavior and the content of moral norms. For instance, Barrett et al (2016) found that across societies, including small-scale societies, humans take an agent's reason for action into account for moral judgments, but they also found independent variation when looking at specific contents, e.g., harm vs. theft, or in how the content influences the role of intentionality. Furthermore, even if conformist transmission could in principle stabilize a variety of behaviors and norms (Chudek and Henrich, 2011), there appears strong canalization in that some kinds of content (such as for instance not to harm others, or engage in parental investment) are more readily considered moral than others (van Schaik, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, some have proposed that morality is determined by the perceived motive of the act [48]. Likewise, evidence suggests that intent perception is a cross-cultural determinant of moral judgements [49]. The mitigating factor of 'necessity' (doing harm to help another) exhibited universal applicability in the severity of moral judgements (across nine societies).…”
Section: Distinguishing Morality From Amorality (Motivation)mentioning
confidence: 99%
“…One reason for this variation may be that individuals and groups have different views about what a person could control or ought to know. Barrett et al (1) acknowledge that they cannot explain the observed pattern of variation in the status of actions and mistakes, across cultures and contexts; devising and testing potential explanations will be a key challenge for future research.…”
Section: Convergence Of Two Approachesmentioning
confidence: 99%
“…Indeed, the burden of proof seems to be on the other side: Is there anything universal about human moral cognition? In PNAS, Barrett et al (1) test one candidate for a universal principle of human morality: that an action's moral value depends not only on the action's consequences but on the person's intentions.…”
mentioning
confidence: 99%